Teaching of ESD phenomena to power electronics students - Dürbaum, Thomas; et al. (2005)
Reliability and interference immunity are always important issues in power electronics systems. Modern power electronic components are often very sensitive towards electrostatic discharge effects. For power electronic engineers basic knowledge of ESD phenomena and protection precaution against ESD destruction is mandatory.This paper describe a set of low cost experiments for a lab. The aim of this lab is to teach graduate power electronic students the basic source and the further behaviour of electrostatic discharge as well as functional operation faults in an example circuit and fully deterioration and destruction of power semiconductors. All experiments described in the paper are very simple but show some effects quiet nicely. The lab circuits themselves are designed really robust against ESD stress to provide a long lifetime. The main goal of all experiments is to animate the students to think about ESD and to demonstrate the relevance of ESD-protection.